Regulatory focus, nutrition involvement, and nutrition knowledge - Pillai, K.G.; Liang, Y.-S.; Thwaites, D.; Sharma, Piyush; Goldsmith, R. (Elsevier, 2019)
Few studies have examined the antecedents of nutrition involvement. Similarly, conflicting results have been recorded on the relationship between nutrition involvement and knowledge, knowledge and dietary behaviors, and nutrition involvement and dietary behaviors. This paper addresses these research gaps by exploring the role of regulatory focus as an antecedent of nutrition involvement. It also examines the effect of nutrition involvement on nutrition knowledge and the effects of both involvement and knowledge on diet adjustment. A large-scale study with 1125 Taiwanese consumers demonstrates a positive effect of promotion focus and no significant effect of prevention focus, on nutrition involvement. Sex and income moderate the effect of promotion focus on nutrition involvement, which in turn has positive effects on nutrition knowledge and diet adjustment. Nutrition knowledge also has a positive effect on diet adjustment. The study clarifies these relationships and provides suggestions to policy making.